71 Integrated Spatial Multi-omics Reveals Tumour Immune Microenvironment Programmes Underlying Durable Response and Resistance to Dual ICI Therapy in ccRCC - Zayd Tippu; Anne-Laure Cattin; Matouš Elphick; Kevin Mulder; Laura Marandino; Barbara Ibarzo Yus; Edward Arbe-Barnes; Sara Lopez Tamargo; Elizabeth Appleton; Stephanie Hepworth; Nisha Bhardwaj; Teena Thakur; et al. (The Oncologist, 2026)
Abstract Background Combination immune checkpoint inhibitor (ICI) approaches are now standard of care for advanced clear cell renal cell carcinoma (ccRCC), yet validated biomarkers to guide selection of optimal combination regimens remain lacking. A key rationale for combined PD-1/CTLA-4 inhibition is the subset of patients achieving durable responses. The tumour immune microenvironment (TiME) is increasingly recognised as a key determinant of this benefit, yet its cellular composition, functional state and spatial organisation, and how these evolve under dual ICI therapy, remain undefined. Methods Tumour specimens from 30 metastatic ccRCC patients across two independent cohorts (TRACERx Renal and the Netherlands Cancer Institute; NKI) were subject to longitudinal multi-modal profiling, all of whom underwent deferred cytoreductive nephrectomy following treatment with combined CTLA-4 (Ipilimumab) and PD-1 (Nivolumab) inhibition. Patients were classified as durable responders (DR; no documented progression event; median follow-up 40.8 months) or as having acquired resistance (AR; initial CR/PR/SD > 6 months prior to progression). Where available, matched pre-treatment biopsy material and multi-regional post-treatment surgical specimens underwent multi-modal spatial profiling (n = 116 tumour regions), co-registering high-plex protein imaging (66-plex antibody panel; Akoya PhenoCycler), with spatial transcriptomics (RNA in situ platform targeting 480 kidney tumour-specific genes; 10x Genomics Xenium) on the same tissue sections, enabling simultaneous protein and transcriptomic characterisation of the TiME at single-cell resolution. In a subset (n = 8; n = 28 tumour regions), single-cell RNA sequencing with paired TCR and BCR sequencing was performed to resolve treatment-induced clonotypic and phenotypic dynamics within T and B cell compartments. Results Dual ICI therapy induced consistent immune remodelling across the cohort irrespective of response, characterised by increases in B cells and CD8+ T cells and a reduction in monocytes/macrophages. At baseline, durable response was associated with increased pericyte coverage of tumour vasculature, whilst acquired resistance patients exhibited decreased pericyte coverage alongside elevated CD39 expression on tumour endothelial cells, implicating dysfunctional, immunosuppressive vasculature as an early determinant of resistance. Post-treatment, durable responders demonstrated enrichment of CCR7+ dendritic cell (DC) niches containing CD4+ T cells, CD8+ T cells and B cells across tumour and stromal compartments, alongside monocytes/macrophages and NK cells within tumour regions. By contrast, acquired resistance CCR7+ DC niches lacked specific immune cell enrichment, displayed dysregulated transcriptional programmes. Acquired resistance was further characterised by enrichment of TREM2+ immunosuppressive macrophages and peri-vascular spatial interactions between macrophages and CD4+ T cells, defining an immunosuppressive niche. scRNA-seq with paired TCR sequencing identified novel and shared memory/resident T-cell clonotypes enriched in durable responders, whilst clonally expanded IgG2 plasma cells were orthogonally validated by BCR sequencing and spatial profiling as a hallmark of durable response. Conclusions Using an integrated multi-omic spatial framework combining high-plex proteomics, single-cell and spatial transcriptomics, we provide a comprehensive characterisation of TiME remodelling under dual ICI therapy in ccRCC. Durable response is preceded at baseline by a normalised vascular phenotype and is subsequently characterised post-treatment by the presence of coordinated CCR7+ DC niches, clonally expanded IgG2 plasma cells, and the emergence of memory/ resident T-cell clonotypes. Conversely, acquired resistance is characterised by an immune exclusion programme, defined by dysfunctional vasculature, TREM2+ macrophage enrichment, impaired DC niche organisation and peri-vascular immunosuppressive niches. By identifying spatially resolved cellular niches underpinning differential responses to combination ICI approaches, this work provides insights into biomarkers of durable response, whilst providing a framework for rational combination strategies to overcome resistance.